Small strain based method for predicting three-dimensional soil displacements induced by braced excavation. (February 2016) - Mu, Linlong; Huang, Maosong
Highlights: Small strain behavior of soil is considered to calculate soil movement. Soil parameters used in FEM is carefully identified by inverse analysis. New method for evaluating soil movement induced by braced excavation is proposed. Underground soil movement induced by excavation can be calculated by the method. Abstract: Displacement control is a critical indicator of foundation design. Maximum deformations of soil induced by excavations are controlled by the allowable deformations of the adjacent structures. In order to evaluate potential damage of surrounding structures, Finite Element Method (FEM) is commonly adopted, predicting soil responses caused by excavations. As the numerical results obtained from FEM are greatly influenced by input material parameters of soil, inverse analysis is an effective method to obtain these parameters, which is based on the results of on-site testing. In this paper, inverse analysis based on the data of on-site testing considering Chicago clays is firstly conducted to get material parameters of soil. Then, with these input parameters, considering Hardening Soil model with Small Strain stiffness (HSS model), FEM program PLAXIS is used for parameter studies, producing coefficients in the equations of attenuation law of the displacements of the soil. Finally, considering the coupled relationship between the soil and the retaining wall, an empirical method is proposed by the authors to predict the three-dimensional displacements of soil induced by braced excavations. Validation has been done by comparisons between the results obtained by the proposed method and by other methods in the literature.